World Association for Bronchology and Interventional Pulmonology (WABIP) guidelines on airway stenting for benign central airway obstruction - Chaddha, Udit; Agrawal, Abhinav; Murgu, Septimiu; Ghori, Uzair; Trias-Sabria, Pere; Ortiz-Comino, Rosamaria; Dutau, Herve; Freitag, Lutz; Gasparini, Stefano; Lee, Pyng; Dooms, Christophe; Trisolini, Rocco; et al. (Respirology, 2025)
Benign central airway obstruction (BCAO) related strictures include post-intubation tracheal stenosis, post-tracheostomy tracheal stenosis, post-surgical or anastomotic stenosis, stenosis related to inflammatory disorders or infectious disorders, chemical injury or post radiotherapy. Techniques and thresholds for airway stenting for each of these unique conditions vary significantly across centres due to lack of guidance. The management of the airway stents once placed due to scarcity of data also has a similar knowledge void. This document aims to address these knowledge gaps by addressing relevant questions related to airway stenting in BCAO. A multidisciplinary, international group of 20 experts from 19 institutions across 12 countries with extensive experience in airway stenting in BCAO was convened as part of this guideline document through the World Association of Bronchology and Interventional Pulmonology (WABIP). A literature search was performed for reports addressing eight clinically relevant PICO questions. Recommendations addressing these questions were formulated using a systematic process involving the evaluation of published evidence, supplemented with expert experience when necessary. The panel participated in the development of the final recommendations using a modified Delphi technique.
Zuerst veröffentlicht: 27. Juni 2025
Gesehen am 10.11.2025